COMPARATIVE STUDY TOXICITY LC 50 AFLATOXIN, OCHRATOXIN, ZEARALENON IN PEANUT (Arachis Hypogaea L) - R.Haryo Bimo Setiarto (Widyariset, 2011)
Afl atoxin, ochratoxin, zearalenon is a compound resulted from metabolism process Aspergillus fl avus, As-pergillus ochraseaus and Fusarium graminearum which grows in moist peanut. A long period and over dose of afl atoxin, ochratoxin, zearalenon can be caused liver cancer, cirrhosis, carsinoma, chronic hepatitis, jaundice, food absorption disturbance, digestion disturbance and immunosuppressive. This research have focused on com-parative study about toxicity afl atoxin, okhratoxin and zearolenon compound. The result of toxicity test by using Artemia salina, it was knowingly detected that LC50 value from crude extract peanut of ochratoxin, zearalenon, afl atoxin was 296.82 ppm, 366.28 ppm, 251.55 ppm respectively. Finally it can be concluded that afl atoxin com-pound from peanut sample had toxicity effect of the most dangerous than other compound (ochratoxin, zearolenon) due to lethal 50% Artemia salina population in smallest concentration.